Implementation of TNI Driving License (SIM) in Army Military Police Units at Denpom IV/3 Salatiga - Mardiyono (GoAcademica Research & Publishing, 2023)
The aim of this research is to describe the implementation of the TNI SIM implementation and describe the obstacles or obstacles and efforts to overcome them, in implementing the TNI SIM at the Ground Forces Military Police Unit Denpom IV/3 Salatiga. This research uses purposive sampling and snowball sampling techniques, with data collection methods in the form of observations and interviews through primary and secondary data sources. The results of the research found that the implementation of the TNI SIM at Denpom IV/3 Salatiga was carried out well, but there were still obstacles or obstacles, where the location of several Korem 073/Makutarama Rank Units was very far from Denpom IV/3 Salatiga, so it took a long time to travel to get there. to the goal, to overcome these obstacles or obstacles, Denpom IV/3 Salatiga carries out socialization on the implementation of TNI SIMs to distant units once a year and if there is a request from the applicant unit.